Real-Time 2.2-Gb/s Water-Air OFDM-OWC System With Low-Complexity Transmitter-Side DSP - Shao, Yingjie; Deng, Rui; He, Jing; Wu, Kaiquan; Chen, Lian-Kuan (Journal of lightwave technology, 2020)
Underwater optical wireless communication (UOWC) is of great interest to the academic and the industry community. In this article, we propose a low-complexity and effective joint transmitter-side digital signal processing (DSP) including geometric shaping, time-domain tone reservation (TR), and clipping. The peak-to-average power ratio reduction performance and implementation complexity of the proposed time-domain TR are extensively analyzed. We then develop a real-time 2.2-Gb/s system, which is optimized for its shaping ratio and clipping ratio. With the help of the efficient DSPs, an 8-dB received optical power enhancement is realized under the bit-error-rate threshold of 3.8 × 10 −3 . We successfully demonstrate a time-multiplexed four 4K video transmission in real-time using the proposed scheme over a 3.6-m underwater and 8-m free-space channel. The implementation details, as well as the analyses of system stability, resource utilization, and latency, are presented. The results validate the feasibility and effectiveness of the proposed scheme and a 2.2-Gbit/s real-time OWC system is demonstrated for a water-air communication link.